L12‐Strengthened Co‐Rich Alloys for High‐Temperature Structural Applications: A Critical Review. Issue 10 (16th September 2021) - Cao, Boxuan; Zhao, Yilu; Yang, Tao; Liu, Chain Tsuan
Abstract : Tremendous efforts have been made to accelerate the design of advanced high‐temperature structural materials, leading to the development of high‐performance Ni‐based superalloys with both superior thermal stability and creep resistance. However, further gains in the temperature capabilities are difficult to achieve due to the narrow gap between the γ′‐solvus temperature and their melting temperatures within Ni‐based superalloys. Given the 50–150 °C advantages in the melting points of Co‐rich alloys than those of the Ni‐based superalloys, as well as the discovery of L12 precipitates in the ternary Co–Al–W alloys, the L12 ‐strengthened Co‐rich alloys are immediately recognized as the promising candidates to be developed as next‐generation high‐temperature structural materials. Follow‐up studies indicate that they also preserve a mild segregation tendency during solidification and superior particle coarsening resistance as compared with Ni‐based superalloys. Promising research directions in the field of Co‐rich high‐temperature alloys are also discussed herein, including thermodynamic‐guided alloy design, grain boundary characteristics, and their correlations with mechanical properties, as well as unique deformation mechanisms and particle shearing configurations. Abstract : Herein, recent advances in developing L12 ‐strengthened Co‐rich alloys for elevated temperature applications are briefly summarized, including outstanding mechanical performance and superior coarsening resistance as compared with Ni‐based superalloys. Promising research directions in developing Co‐rich high‐temperature alloys are also introduced, including thermodynamic‐guided alloy design, grain boundary characteristics and their correlations with mechanical properties, and unique deformation mechanisms and particle shearing configurations.